Don Juan und kalte Liebe - Szczepaniak, Monika (Studia Germanica Posnaniensia, 2015)
The present article is an attempt to use the metaphorical category of temperature in the interpretation of literary creations of love in two different cultural contexts: against the background of the emotional culture of the inter-war period as well as of the present time. The analysis focusses on two literary texts: Don Juan kommt aus dem Krieg (1936) by Ödön von Horváth as well as Don Juan de la Mancha (2007) by Robert Menasse, which encourage to reflect on remarkable transformations of the culture of love and the positioning of both men and women within the new emotional styles.